Maternal serum alpha-fetoprotein levels in fetal hydrocephalus: a retrospective population based study - MacDonald Karen M; Chodirker Bernard N; Szajkowski Terrence P; Evans Jane A (BMC, 2006)
Abstract Background Although maternal serum alpha-fetoprotein (MSAFP) is a highly sensitive marker for certain congenital malformations such as open neural tube and ventral wall defects, its usefulness as a screening test for fetal hydrocephalus is uncertain. We wished to determine the distribution of maternal serum alpha-fetoprotein levels associated with fetal hydrocephalus in a population-based screening program in Manitoba, and their potential relationship to additional anomalies. Methods Cases of fetal hydrocephalus unrelated to neural tube defects were ascertained from multiple sources and reviewed. Cross-reference with the Manitoba Maternal Serum Screening Program database determined which mothers had undergone maternal serum screening. Mean MSAFP levels in both isolated and complex hydrocephalus were calculated and compared with the general population of screened pregnancies using Independent Samples T-tests. Results Mean MSAFP levels in 70 cases of fetal hydrocephalus were significantly higher than those of the general population of screened pregnancies (P = 0.029). This was due to the fact that mean MSAFP levels in those cases with other major anomalies were increased over those of the general population (P = 0.041); cases with hydrocephalus alone showed no significant difference (P = 0.203). Only seven cases (10%) had MSAFP levels ≥ 2.3 multiples of the median, the cut-off used in Manitoba. However, six of these (86%) had additional major and/or minor malformations. Conclusion MSAFP screening has low sensitivity for fetal hydrocephalus and is rarely elevated in isolated cases. However, when fetal hydrocephalus is detected, elevated MSAFP levels indicate that the fetus is at significant risk to have additional malformations and further investigations, including chromosome breakage studies, may be indicated.